PENGARUH ASET, PEMBERIAN KREDIT DAN PERMODALAN TERHADAP LABA PERBANKAN DI INDONESIA (Studi Empiris Bank Umum Konvensional Yang Terdaftar di Bursa Efek Indonesia) - Syafrudin Syafrudin (Universitas Batanghari Jambi, 2014)
The purpose of research is to investigate and analyze the influence of Asset , Capital Lending and significant effect on the profit on Banking in Indonesia In Simultaneous or partially. Further research method diganakan role in research with quantitative research method approach that inferential statistics are supported by empirical data obtained from financial statements published by Bank Indonesia through the website www.bi.go.id. and analyzed by multiple regression analysis approach is a portrait of the relationship between the independent variable ( in this case Assets , Loans and Capital ) of the dependent variable ( in the case in is profit ) , with a model of multiple regression equation Y = a + BX1 + CX2 + DX3 , where the variable Y = income , assets X1 = X2 = X3 = credit and Capital , a = intercept or constant and bcd = regression coefficient of each independent variable . By testing the hypothesis that the results obtained are simultaneous F-test result that the calculated F value 1766.834 with a significance of 0.000 . were higher than the value of F table ( one side or α = 0.05 ) is 3.14 ( or 1766.834 > 3.14 ) , so the hypothesis in this study stated that the Assets , Capital Lending and Banking significant effect on earnings simultaneously in Indonesia is proven . And testing hypotheses obtained partial results : no significant effect on the Assets of Banking Income . Non-productive assets significantly influence the Banking Profit is proven , or H0 is rejected . RWA significant effect on Banking Profit is proven , or H0 is rejected . But its influence is negative , where the increasing amount of RWA actually reduce bank profitability and vice versa . Loans disbursed significant effect on Banking Profit is not proven , or H0 is accepted . Credit Loss significant effect on Banking Profit is proven , and significant effect on earnings Equity Bank is proven .Keywords: Assets, Credit, Capital and Profit Banking